Antara Tradisi dan Modernisasi: Dinamika Pedagang Batik di Pasar Klewer pada Masa Orde Baru - Rohmawati, Alyah; Utami, Carolina Santi Muji (SENTRI: Jurnal Riset Ilmiah, 2026)
This research aims to examine how batik traders in the Surakarta Klewer Market carry out trading activities in the midst of the pressure of modernization and the policies of the New Order regime. Klewer Market, which initially grew from traditional trading practices in Slompretan Market, grew rapidly in the 1968-1970s period until it became the largest batik and textile wholesale center in Central Java, built in the form of a multi-storey market inaugurated by President Soeharto. Research shows how batik traders maintain a network of traditional socio-economic relations, such as direct relationships with artisans and fluid bargaining patterns, while at the same time adapting modern business methods, such as wholesale sales systems, permanent kiosk arrangements, and more formal market arrangements. The dynamics asserts that modernization during the New Order did not immediately replace tradition, but created a new form of batik trading practice that was rooted in local wisdom but arranged in a more orderly market structure.